Performance and emissions of internal combustion engine using different blends of ethanol-gasoline - Jaramilla, Melchor Estero 1975- (2009)
A number of environmental and economic benefits have been claimed for biofuels. Existing reports present different information regarding the effect of these biofuels to engines. It always leaves a big question and debate among concerned, especially to oil producers ans consumers, for the lack of a concrete and general recommendation that can be adopted universally. The Philippines Government Alternative Fuel Program now requires local oil companies to sell gasoline pre-blended with ten percent ethanol and urged motorist to switch to this fuel. However, no local study has been done to support this campaign. This research investigated experimentally the effects of different ethanol-gasoline blend from 0% to 30% biofuel on a spark-ignition engine for performance and emissions using the Japanese 10-15 mode drive cycle at road load simulation. This was accompanied by a steady state test and a maximum power measurement in an AVL chasis dynamometer with a Semtech-DS emissions analyzer to establish better picture of the use of bioethanol fuel which, in turn, will be used as a guide in creating more substantial government policies and regulations. The engine test showed a positive correlation between specific fuel consumption and ethanol amount in the fuel mixture. There was a slight increase of power obtained for E5, E12.5, E20 and E25 of about 1.9%, 0.55%, 1.64% and 3.4% respectively while E10 and E15 produced decrease in outputs of 0.78%, and 0.32% respectively which are all considered very comparable to E0 data. Emission test results showed that the E5 blend resulted to the highest increase in carbon monoxide emission of about 45.6% while a gradual reduction in the latter was observed with increase in ethanol concentration. E25 showed the highest decrease of about 29% compared to neat. All CO concentrations in different blends conform to the Philippine Clean Air Act. Co2 emission was very similar to CO trend where the E5 gave the highest emission of about 83.73 g/km while the other blends in increasing ethanol content was shown a decreasing trend. E25 gave the lowest at about 49.26 g/km. Unburned Hydrocarbon showed a gradual increasing trend from E0to E15. Surprisingly, an abrupt increase at E20 by 239%, went down at E25 (with only 37.99%) and went up with 90% at E30, compared all to neat data. Notice also that ethanol addition did not influence NOx emission due to non-significant characteristics. The combined unburned HC and NOx in all blends exhibited lower values compared to mandate of the law. Constant velocity tests data showed that effects of ethanol was not as evident compared to the results at drive cycle test.